Factors Influencing Interest in Applying for Ultra-Micro Financing for Female UMK Entrepreneurs in the Special Region of Yogyakarta - Herowati, Erlina (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Micro, small and medium enterprises (MSMEs) are the pillars of the Indonesian economy. Its contribution to the national economy is enormous. This sector is known to be the largest provider of employment opportunities and an important player in local economic development. To develop a business, capital and good management are needed, but there is still a lot of capital that has not been touched by bank financial institutions. Microfinance Institutions (LKM) in Indonesia are financial institutions whose function is to help the activities of Micro, Small and Medium Enterprises (MSMEs) to progress further. This research aims to analyze the factors that influence interest in applying for ultra-micro financing for female micro-small entrepreneurs in the Special Region of Yogyakarta. The research was conducted using descriptive qualitative research methods with primary and secondary data. Primary data was obtained through a questionnaire survey of female micro business actors who received financing from Mekar Madani, Gramindo and Amartha with a sample of 60 people taken purposively. Research results using a regression model. The t test and f test show that accessibility, interest rates and economic needs have a positive effect on interest in applying for ultramicro financing with an R value of 0.315, 0.279 and 0.390 respectively and a significance value of <0.05 based on the simultaneous test (f test), variables of accessibility, interest rates and economic needs together have a positive influence on the increasing interest of female MSEs in applying for ultramicro financing with an R value of 0.526 and a significance value of <0.05.